Priorities for research to support local authority action on health and climate change: a study in England - Pete Lampard; Shainur Premji; Joy Adamson; Laura Bojke; Karen Glerum-Brooks; Su Golder; Hilary Graham; Dina Jankovic; Dagmar Zeuner (BMC, 2023)
Abstract Background Evidence is needed to support local action to reduce the adverse health impacts of climate change and maximise the health co-benefits of climate action. Focused on England, the study identifies priority areas for research to inform local decision making. Methods Firstly, potential priority areas for research were identified from a brief review of UK policy documents, and feedback invited from public and policy stakeholders. This included a survey of Directors of Public Health (DsPH) in England, the local government officers responsible for public health. Secondly, rapid reviews of research evidence examined whether there was UK evidence relating to the priorities identified in the survey. Results The brief policy review pointed to the importance of evidence in two broad areas: (i) community engagement in local level action on the health impacts of climate change and (ii) the economic (cost) implications of such action. The DsPH survey (n = 57) confirmed these priorities. With respect to community engagement, public understanding of climate change's health impacts and the public acceptability of local climate actions were identified as key evidence gaps. With respect to economic implications, the gaps related to evidence on the health and non-health-related costs and benefits of climate action and the short, medium and longer-term budgetary implications of such action, particularly with respect to investments in the built environment. Across both areas, the need for evidence relating to impacts across income groups was highlighted, a point also emphasised by the public involvement panel. The rapid reviews confirmed these evidence gaps (relating to public understanding, public acceptability, economic evaluation and social inequalities). In addition, public and policy stakeholders pointed to other barriers to action, including financial pressures, noting that better evidence is insufficient to enable effective local action. Conclusions There is limited evidence to inform health-centred local action on climate change. More evidence is required on public perspectives on, and the economic dimensions of, local climate action. Investment in locally focused research is urgently needed if local governments are to develop and implement evidence-based policies to protect public health from climate change and maximise the health co-benefits of local action.